Kinetics and mechanism for thermal and photochemical decomposition of 4, 4′-azobis(4-cyanopentanoic acid) in aqueous media. Issue 24 (20th May 2019) - Zhou, Yanyan; Zhang, Zhengbiao; Postma, Almar; Moad, Graeme
Abstract : The two diastereoisomers of 4, 4′-azobis(4-cyanopentanoic acid) decompose at different rates in aqueous media. The major products (>50%) are amides produced by trapping the ketenimines formed by C–N coupling. Abstract : 4, 4′-Azobis(4-cyanopentanoic acid) comprises two diastereoisomers that decompose at different rates in aqueous media [ racemic -ACPA: E a = 132.2 kJ mol −1, A = 4.76 × 10 15 s −1, 10 h t 1/2 = 65 °C; meso -ACPA: E a = 131.7 kJ mol −1, A = 2.98 × 10 15 s −1, 10 h t 1/2 = 67 °C], but both decompose at a similar though faster rate in N, N -dimethylformamide [ E a = 134.0 kJ mol −1, A = 1.26 × 10 16 s −1, 10 h t 1/2 = 63 °C]. The major product of decomposition in both aqueous and organic media is the ketenimine formed by C–N coupling of the radicals formed, which is irreversibly trapped as an amide in aqueous media.